A novel Co/TiO2 nanocomposite derived from a metal–organic framework: synthesis and efficient microwave absorption. Issue 9 (12th February 2016) - Zhang, Xingmiao; Ji, Guangbin; Liu, Wei; Zhang, Xingxin; Gao, Qingwen; Li, Yuchun; Du, Youwei
Abstract : Two coated titanium oxide (TiO2 ) routes are designed to prepare core–shell Co@NPC@TiO2 (NPC: nanoporous carbon) and C–ZIF-67@TiO2 (ZIF-67: zeolitic imidazolate framework-67) with a multi-interfaced yolk–shell structure. Abstract : To overcome the shortcomings (poor impedance mismatching and weak electromagnetic wave attenuation) of the Co nanoparticles embedded into nanoporous carbon (Co@NPC) derived from the thermal decomposition of zeolitic imidazolate framework-67 (ZIF-67), two coated titanium oxide (TiO2 ) routes are designed to prepare core–shell Co@NPC@TiO2 and multi-interfaced yolk–shell C–ZIF-67@TiO2 (obtained from the thermal decomposition of ZIF-67@TiO2 ) structures. The permittivity and permeability of C–ZIF-67@TiO2 significantly depend on the thickness of the TiO2 shell in ZIF-67@TiO2, and the thickness of the TiO2 shell in the as-obtained samples can be easily controlled via changing the addition content of tetrabutyl titanate in the hydrolyzation process. The as-prepared samples have remarkable absorbing characteristics in wide frequency bands from 2–18 GHz with thicknesses of 1.0–5.0 mm. 50 wt% of the C–ZIF-67@TiO2 -2 (the addition amount of tetrabutyl titanate is 2 mL) nanocomposite filled within paraffin shows a maximum reflection loss (RL) of −51.7 dB at an absorbing thickness of 1.65 mm, meanwhile, for the Co@NPC@TiO2 -1.2 (the addition amount of tetrabutyl titanate is 1.2 mL) nanocomposite, a maximum RL can be achieved of −31.7 dB at 1.5 mm. This study provides a good reference for the future preparation of other carbon-based lightweight microwave absorbing materials derived from metal organic frameworks.